"Johnny Poppers": a cause of serious ocular injury. Issue 7 (1st July 1998) - MacAndie, Kerr; Kyle, Peter
Abstract : AIMS/BACKGROUND: The causes of blunt ocular trauma are many and diverse. We present two cases of ocular injury caused by an unusual form of weapon called a "Johnny Popper". There follows a theoretical and experimental evaluation of the velocity of the projectiles fired by this device. METHODS: A Johnny Popper was constructed under expert guidance. The elastic properties of the device were measured and this allowed calculation of a theoretical exit velocity of the projectiles fired. The weapon was subsequently fired under test conditions which permitted the exit velocity of the projectiles fired to be measured directly. RESULTS: The theoretical velocity of the projectiles was calculated as 80 ms -1 and the experimentally measured velocity was 57 ms -1 . CONCLUSIONS: Johnny Poppers are a previously undescribed and unique form of home made weapon. They are intended for playful mischief, but have the potential to cause serious ocular trauma.